D.W. Thinks Big - Brown, Marc Tolon (Boston : Joy Street Books, 1993)
Even though her brother Arthur says she is too little to help with the upcoming wedding, D.W. proves she is just the right size when disaster strikes during the ceremony.
Keywords: Weddings -- Fiction; Size -- Fiction; Brothers and sisters -- Fiction; Aardvark -- Fiction